Heart rate during work and heart rate variability during the following night: a day-by-day investigation on the physical activity paradox among blue-collar workers - Korshøj, Mette; Lund Rasmussen, Charlotte; de Oliveira Sato, Tatiana; Holtermann, Andreas; Hallman, David (Scandinavian Journal of Work, Environment & Health, 2021)
' ' OBJECTIVES ': 'Contrary to leisure-time physical activity, occupational physical activity (OPA) may have harmful health effects, called the physical activity paradox. A proposed mechanism is that OPA can elevate the heart rate (HR) for several hours per day. We aimed to investigate the association between the mean intensity of OPA and HR variability (HRV) indices the following night. ' ' METHODS ': 'Three cohorts (NOMAD, DPhacto, and Physical Workload and Fitness) involving blue-collar workers from different sectors were merged in this study. HR monitors (Actiheart) recorded 24-hour inter-beat intervals (IBI) for up to four consecutive days. The relative intensity of the mean HR during work was estimated by HR reserve (%HRR), and time-domain indices of HRV were analyzed during the following night. Data were analyzed using a multilevel growth model to test the association between mean %HRR during work and HRV indices at night in a day-by-day analysis adjusted for age, BMI, alcohol consumption, smoking, and occupation. ' ' RESULTS ': 'The dataset included a sample of 959 Danish blue-collar workers, with a mean %HRR during work of 31%, and 42% worked at an intensity ≥30%HRR. The multilevel model showed negative within- and between-subject associations between %HRR during work and HRV indices at night. ' ' CONCLUSIONS ': 'Our results indicate a higher %HRR during work to associate with lower HRV indices the following night and a higher HR, reflecting an imbalanced autonomic cardiac modulation. This finding supports a high mean HR during work to be a potential underlying mechanism for the harmful health effect of OPA.
Keywords: aerobic workload; autonomic nervous system; blue-collar worker; heart rate; heart rate reserve; heart rate variability; physical activity